Pengaruh Pendidikan kewarganegaraan terhadap pembentukan identitas nasional anak muda - kuszayanah, risa kuszayanah (Maliki Interdisciplinary Journal, 2025)
Education is a strong foundation for every individual or group that is useful for guiding or building their respective characters. In Indonesia, education is very important and dominant for every student. Education itself here refers to the meaning of conscious and planned efforts to develop the potential of students. In addition to developing the potential of students, education is also a place to form good character for the nation because young people are the next generation of the nation. In today’s era, the development of technology and globalization has a great influence on society. Therefore, Civic Education is highly emphasized in Indonesia as a mandatory lesson for every level from elementary school to college. This is part of the country’s goal to protect the country and nation of Indonesia from damage or destruction of new changes in the country, whether from the development of the times or because of factors of its own citizens because they do not have an education. In addition to taking education, students also need to implement this education in their daily lives as an example of the community environment. Through social activities in the community, students can implement it as citizens who are responsible for their country. These social activities can be carried out starting from mutual cooperation, social service activities, participating in elections, participating in religious study activities and so on.